A wear-resistant polymer material and preparation method thereof
By using mineralized polypeptides and bone morphogenetic protein-induced mineralizing agents in polymer materials, an ordered mineral phase structure is formed, which solves the problems of non-degradable plastic pollution and insufficient performance of degradable materials, and achieves high-performance wear resistance The preparation of polymer materials meets the application needs of plastic parts.
Patent Information
- Application Number
- CN202410737416.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-06-07
AI Technical Summary
Existing non-degradable plastic parts cause environmental pollution after use, and the physical and mechanical properties of the degradable plastic materials are difficult to meet practical application requirements, especially the friction and mechanical properties are insufficient.
Using an abrasion-resistant polymer material, the formulation includes polyurethane resin, nanocellulose, plant fibers, mineral powders, plasticizers, fillers, lubricants and mineralizers, to induce peptides and bone morphogenesis proteins through mineralization. Combination promotes the orderly arrangement and deposition of mineral powders in polymer materials, forming a strong and wear-resistant structure.
It significantly improves the wear resistance and strength of polymer materials, forms an orderly mineral phase structure, optimizes the mechanical properties and friction properties of the materials, and meets the stable and efficient working needs of plastic parts in various application scenarios.
Smart Images

Figure BDA0004882201180000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a wear-resistant polymer material and a preparation method thereof. Background Art
[0002] In the current market, plastic parts have become an indispensable part of many industries. However, it is regrettable that most of these plastic parts are made of non-degradable materials, which is undoubtedly contrary to the growing environmental awareness. Traditional non-degradable plastics often cause serious environmental pollution after long-term use, which is not in line with the pursuit of sustainable development in modern society. In response to the call for environmental protection, some people have proposed to use degradable materials to manufacture plastic parts. However, although this material is environmentally friendly, its physical properties, mechanical properties, especially friction properties and mechanical properties, are often difficult to meet the requirements of practical applications. This means that simply pursuing the degradability of materials cannot fully meet the industry's demand for the performance of plastic parts. Therefore, we urgently need to develop a new type of wear-resistant polymer material. This polymer material should not only have degradable environmental characteristics to reduce the negative impact on the environment, but also have excellent friction and mechanical properties to ensure that the manufactured plastic parts can work stably and efficiently in various application scenarios. Summary of the invention
[0003] In view of this, the present invention proposes a wear-resistant polymer material and a preparation method thereof to solve the above problems.
[0004] The technical solution of the present invention is achieved as follows: a wear-resistant polymer material comprises the following raw materials in parts by weight: 30-50 parts of polyurethane resin, 5-15 parts of nanocellulose, 10-20 parts of plant fiber, 20-40 parts of mineral powder, 5-10 parts of plasticizer, 5-10 parts of filler, 3-5 parts of lubricant, and 3-5 parts of mineralizer, wherein the mineralizer comprises bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid.
[0005] Furthermore, the plant fiber is one or a combination of palm fiber, coconut shell fiber, bamboo fiber, straw fiber, abaca fiber, flax fiber, sisal fiber, kapok fiber and cotton fiber.
[0006] Furthermore, the mineral powder is one or a combination of barite powder, corundum powder, feldspar powder, wollastonite powder, mica powder, talc powder, and quartz powder.
[0007] Furthermore, the plasticizer is one of dibutyl phthalate, epoxy soybean oil, dioctyl sebacate, trioctyl trimellitate, triethyl citrate, and chlorinated paraffin.
[0008] Furthermore, the filler is one or a combination of nano-silicon dioxide, carbon fiber, glass fiber, and aluminum borate whisker.
[0009] Furthermore, the lubricant is one or a combination of silicone oil, glycerin, fatty acid amide, oleic acid, and silicone powder.
[0010] Furthermore, the mineralizer is composed of bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid in a mass volume ratio of g / mL of (1-3):(4-8):(1-3).
[0011] Furthermore, the mineralization-inducing polypeptide is obtained by the following method: the shells are cleaned, sterilized, and ground into powder to obtain shell powder, the shell powder is placed in a sodium hydroxide solution and soaked for 15-20 hours, the mass volume ratio of the shell powder to the sodium hydroxide solution g / mL is (1.0-1.5):(3.0-5.0), the soaked shell powder is treated with an ultrasonic device, and the ultrasonic treatment is performed for 60-90 minutes under the conditions of ultrasonic power of 200-400W and ultrasonic frequency of 20-40kHz, and the above-mentioned solid-liquid mixture is filtered using a 100-200 mesh sieve, and the filtrate is taken, and the filtrate is extracted with ethanol, and the volume ratio of the filtrate to ethanol is (1.0-1.2):(1.5-2.5), and the polypeptide solution is extracted 2-3 times to obtain a polypeptide solution, and the polypeptide solution is concentrated for 40-60 minutes under the conditions of 0.05-0.10MPa, and freeze-dried at -40 to -60°C for 100-120 minutes to obtain a mineralization-inducing polypeptide.
[0012] Furthermore, a method for preparing a wear-resistant polymer material comprises the following steps:
[0013] S1. Weigh the polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, and lubricant in proportion, and stir at 300-500 r / min for 10-20 min to obtain a mixture Ⅰ;
[0014] S2. The mixture Ⅰ is added to a twin-screw extruder for a first melting to obtain a molten material Ⅰ;
[0015] S3. Cool the molten material Ⅰ to 40-50 ℃, add mineralizer and mineral powder, stir at 100-200r / min for 20-30min to obtain a mixture Ⅱ, and put the mixture Ⅱ into a reactor for mineralization reaction;
[0016] S4. Add the mineralized mixture II to the melt granulator for a second melting, and extrude the molten material through the die of the extruder and cut it into granules with a size of 2-4 mm to obtain a wear-resistant polymer material.
[0017] Further, the first melting in S2 is carried out at 150-200°C, and the second melting in S4 is carried out at 180-220°C.
[0018] Furthermore, the mineralization temperature in S3 is 60-80°C, the mineralization pressure is 10-20MPa, and the mineralization time is 4-6h.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention induces the mineralization of polymer materials through a mineralizer composed of bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid, thereby greatly improving the wear resistance and strength performance of the polymer materials. The bone morphogenetic protein induces the mineral components in the mineral powder to form an ordered structure in the polymer material, thereby enhancing the strength and wear resistance of the polymer material. The mineralization inducing polypeptide can promote the orderly arrangement and deposition of the mineral powder in the polymer material matrix, thereby forming a tougher and wear-resistant structure. Ethylenediaminetetraacetic acid controls the release rate of metal ions in the mineral powder through chelation, thereby regulating the kinetics of the mineralization process. At the same time, ethylenediaminetetraacetic acid induces the polymer material to form a mineral phase with a specific structure and morphology through complexation with metal ions, further optimizing the performance of the polymer material. DETAILED DESCRIPTION
[0020] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0021] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0022] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0023] Example 1
[0024] A wear-resistant polymer material comprises the following raw materials in parts by weight: 30 parts of polyurethane resin, 5 parts of nanocellulose, 10 parts of plant fiber, which is palm fiber, 20 parts of mineral powder, which is barite powder, 5 parts of plasticizer, which is dibutyl phthalate, 5 parts of filler, which is nano silicon dioxide, 3 parts of lubricant, which is silicone oil, and 3 parts of mineralizer consisting of bone morphogenetic protein, mineralization inducing polypeptide and ethylenediaminetetraacetic acid, with a mass volume ratio of g / mL of 1:4:1.
[0025] Example 2
[0026] A wear-resistant polymer material comprises the following raw materials in parts by weight: 50 parts of polyurethane resin, 15 parts of nanocellulose, 20 parts of plant fiber, which is coconut shell fiber, 40 parts of mineral powder, which is feldspar powder, 10 parts of plasticizer, which is epoxidized soybean oil, 10 parts of filler, which is carbon fiber, 5 parts of lubricant, which is glycerol, and 5 parts of mineralizer consisting of bone morphogenetic protein, mineralization inducing polypeptide and ethylenediaminetetraacetic acid, with a mass volume ratio of g / mL of 3:8:3.
[0027] The mineralization-inducing polypeptide in Example 1-2 is obtained by the following method: the shells are cleaned, sterilized, and ground into powder to obtain shell powder, the shell powder is soaked in a sodium hydroxide solution for 15 hours, the mass volume ratio of the shell powder to the sodium hydroxide solution g / mL is 1.0:3.0, the soaked shell powder is treated with an ultrasonic device, and the ultrasonic treatment is carried out for 90 minutes under the conditions of ultrasonic power of 200 W and ultrasonic frequency of 20 kHz, and the above-mentioned solid-liquid mixture is filtered with a 100-mesh sieve, and the filtrate is taken, and the filtrate is extracted with ethanol, and the volume ratio of the filtrate to ethanol is 1.0:1.5, and the polypeptide solution is extracted twice to obtain a polypeptide solution, and the polypeptide solution is concentrated at 0.05 MPa for 60 minutes, and freeze-dried at -40°C for 120 minutes to obtain a mineralization-inducing polypeptide.
[0028] A method for preparing a wear-resistant polymer material in Example 1-2 comprises the following steps:
[0029] S1. Weigh the polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, and lubricant in proportion, stir at 300 r / min for 20 min, and obtain a mixture I;
[0030] S2. The mixture Ⅰ is added to a twin-screw extruder and melted for the first time at 150 ℃ to obtain a molten material Ⅰ;
[0031] S3. The molten material I is cooled to 40°C, a mineralizer and a mineral powder are added, and the mixture is stirred at 100 r / min for 30 min to obtain a mixture II, and the mixture II is placed in a reactor, and a mineralization reaction is carried out at a mineralization temperature of 60°C and a mineralization pressure of 10 MPa for 6 hours;
[0032] S4. Add the mineralized mixture II to the melt granulator, melt it for the second time at 180°C, extrude the molten material through the die of the extruder and cut it into granules with a size of 2 mm to obtain a wear-resistant polymer material.
[0033] Example 3
[0034] A wear-resistant polymer material comprises the following raw materials in parts by weight: 40 parts of polyurethane resin, 10 parts of nanocellulose, 15 parts of plant fiber, wherein the plant fiber consists of abaca fiber, cotton fiber and bamboo fiber in a mass ratio of 1:1:1, 30 parts of mineral powder, wherein the mineral powder consists of corundum powder, wollastonite powder and mica powder in a mass ratio of 1:1:1, 8 parts of plasticizer, wherein the plasticizer is dioctyl sebacate, 8 parts of filler, wherein the filler consists of nano silicon dioxide and aluminum borate whisker in a mass ratio of 1:1, 4 parts of lubricant, wherein the lubricant consists of silicone oil and fatty acid amide in a volume ratio of 2:1, and 4 parts of mineralizer, wherein the bone morphogenetic protein, mineralization inducing polypeptide and ethylenediaminetetraacetic acid in a mass-volume ratio (g / mL) of 2:6:2.
[0035] The mineralization-inducing polypeptide is obtained by the following method: cleaning, sterilizing and grinding shells into powder to obtain shell powder, soaking the shell powder in a sodium hydroxide solution for 17.5 hours, wherein the mass volume ratio of the shell powder to the sodium hydroxide solution is 1.2:4.0 g / mL, treating the soaked shell powder with an ultrasonic device, performing ultrasonic treatment for 75 minutes at an ultrasonic power of 300 W and an ultrasonic frequency of 30 kHz, filtering the solid-liquid mixture with a 150-mesh sieve, taking the filtrate, extracting the filtrate with ethanol, wherein the volume ratio of the filtrate to ethanol is 1.1:2.0, extracting three times to obtain a polypeptide solution, concentrating the polypeptide solution at 0.08 MPa for 50 minutes, and freeze-drying at -50°C for 110 minutes to obtain a mineralization-inducing polypeptide.
[0036] The method for preparing a wear-resistant polymer material in Example 3 comprises the following steps:
[0037] S1. Weigh the polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, and lubricant in proportion, stir at 400 r / min for 15 min, and obtain a mixture I;
[0038] S2. The mixture Ⅰ is added to a twin-screw extruder and melted for the first time at 175°C to obtain a molten material Ⅰ;
[0039] S3. The molten material I is cooled to 45°C, a mineralizer and a mineral powder are added, and the mixture is stirred at 150 r / min for 25 min to obtain a mixture II, and the mixture II is placed in a reactor, and a mineralization reaction is carried out at a mineralization temperature of 70°C and a mineralization pressure of 15 MPa for 5 hours;
[0040] S4. Add the mineralized mixture II to the melt granulator, perform a second melting at 200°C, and extrude the molten material through the die of the extruder and cut it into granules of 3 mm in size to obtain a wear-resistant polymer material.
[0041] Example 4
[0042] A wear-resistant polymer material comprises the following raw materials in parts by weight: 30 parts of polyurethane resin, 5 parts of nanocellulose, 10 parts of plant fiber, which is flax fiber, 20 parts of mineral powder, which is talcum powder, 5 parts of plasticizer, which is triethyl citrate, 5 parts of filler, which is glass fiber, 3 parts of lubricant, which is silicone powder, and 3 parts of mineralizer consisting of bone morphogenetic protein, mineralization inducing polypeptide and ethylenediaminetetraacetic acid, with a mass-to-volume ratio of g / mL of 1:4:1.
[0043] Example 5
[0044] A wear-resistant polymer material comprises the following raw materials in parts by weight: 50 parts of polyurethane resin, 15 parts of nanocellulose, 20 parts of plant fiber, wherein the plant fiber consists of sisal fiber and straw fiber in a mass ratio of 1:1, 40 parts of mineral powder, wherein the mineral powder consists of barite powder and quartz powder in a mass ratio of 1:1, 10 parts of plasticizer, wherein the plasticizer is chlorinated paraffin, 10 parts of filler, wherein the filler consists of nano silicon dioxide and glass fiber in a mass ratio of 1:2, 5 parts of lubricant, wherein the lubricant consists of silicone oil, glycerol and oleic acid in a volume ratio of 2:1:1, and 5 parts of mineralizer, wherein the mass-to-volume ratio (g / mL) is 3:8:3, the bone morphogenetic protein, mineralization-inducing polypeptide and ethylenediaminetetraacetic acid are formed.
[0045] The mineralization-inducing polypeptide in Example 4-5 is obtained by the following method: the shells are cleaned, sterilized, and ground into powder to obtain shell powder, the shell powder is soaked in a sodium hydroxide solution for 20 hours, the mass volume ratio of the shell powder to the sodium hydroxide solution g / mL is 1.5:5.0, the soaked shell powder is treated with an ultrasonic device, and the ultrasonic treatment is performed for 60 minutes at an ultrasonic power of 400 W and an ultrasonic frequency of 40 kHz. The solid-liquid mixture is filtered using a 200-mesh sieve, the filtrate is taken, and the filtrate is extracted with ethanol, the volume ratio of the filtrate to ethanol is 1.2:2.5, and the polypeptide solution is extracted three times to obtain the polypeptide solution, the polypeptide solution is concentrated at 0.10 MPa for 40 minutes, and freeze-dried at -60°C for 100 minutes to obtain the mineralization-inducing polypeptide.
[0046] A method for preparing a wear-resistant polymer material in Example 4-5 comprises the following steps:
[0047] S1. Weigh the polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, and lubricant in proportion, stir at 500 r / min for 10 min, and obtain a mixture I;
[0048] S2. The mixture Ⅰ is added to a twin-screw extruder and melted for the first time at 200 ℃ to obtain a molten material Ⅰ;
[0049] S3. The molten material I is cooled to 50°C, a mineralizer and a mineral powder are added, and the mixture is stirred at 200 r / min for 20 min to obtain a mixture II, and the mixture II is placed in a reactor, and a mineralization reaction is carried out at a mineralization temperature of 80°C and a mineralization pressure of 20 MPa for 4 hours;
[0050] S4. Add the mineralized mixture II to the melt granulator, melt it for the second time at 220°C, extrude the molten material through the die of the extruder and cut it into granules of 4 mm in size to obtain a wear-resistant polymer material.
[0051] Comparative Example 1
[0052] Compared with Example 3, the difference between this comparative example and Example 3 is that the raw materials of the wear-resistant polymer material do not include a mineralizer, that is, a wear-resistant polymer material, comprising the following raw materials in parts by weight: 40 parts of polyurethane resin, 10 parts of nanocellulose, 15 parts of plant fiber, and the plant fiber is composed of abaca fiber, cotton fiber, and bamboo fiber in a mass ratio of 1:1:1, 30 parts of mineral powder, and the mineral powder is composed of corundum powder, wollastonite powder, and mica powder in a mass ratio of 1:1:1, 8 parts of plasticizer, and the plasticizer is dioctyl sebacate, 8 parts of filler, and the filler is composed of nano silicon dioxide and aluminum borate whisker in a mass ratio of 1:1, and 4 parts of lubricant, and the lubricant is composed of silicone oil and fatty acid amide in a volume ratio of 2:1.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 3 is that the mineralizer consists of bone morphogenetic protein and ethylenediaminetetraacetic acid in a mass volume ratio of g / mL of 3:3.
[0055] Comparative Example 3
[0056] Compared with Example 3, the comparative example is different in that the raw materials of the wear-resistant polymer material do not include nano cellulose, that is, a wear-resistant polymer material, comprising the following raw materials in parts by weight: 40 parts of polyurethane resin, 15 parts of plant fiber, and the plant fiber is composed of abaca fiber, cotton fiber, and bamboo fiber in a mass ratio of 1:1:1, 30 parts of mineral powder, and the mineral powder is composed of corundum powder, wollastonite powder, and mica powder in a mass ratio of 1:1:1, 8 parts of plasticizer, and the plasticizer is dioctyl sebacate, 8 parts of filler, and the filler is composed of nano silicon dioxide and aluminum borate whisker in a mass ratio of 1:1, 4 parts of lubricant, and the lubricant is composed of silicone oil and fatty acid amide in a volume ratio of 2:1, and 4 parts of mineralizer composed of bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid in a mass volume ratio of g / mL of 2:6:2.
[0057] Comparative Example 4
[0058] Compared with Example 3, the difference between this comparative example and Example 3 is that the raw materials of the wear-resistant polymer material do not include plant fibers, that is, a wear-resistant polymer material, comprising the following raw materials in parts by weight: 40 parts of polyurethane resin, 10 parts of nanocellulose, 30 parts of mineral powder, and the mineral powder is composed of corundum powder, wollastonite powder, and mica powder in a mass ratio of 1:1:1, 8 parts of plasticizer, and the plasticizer is dioctyl sebacate, 8 parts of filler, and the filler is composed of nano silicon dioxide and aluminum borate whiskers in a mass ratio of 1:1, 4 parts of lubricant, and the lubricant is composed of silicone oil and fatty acid amide in a volume ratio of 2:1, and 4 parts of mineralizer composed of bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid in a mass volume ratio of g / mL of 2:6:2.
[0059] Comparative Example 5
[0060] This comparative example is compared with Example 3, the difference is that no mineralization reaction is performed in the preparation method of the wear-resistant polymer material, that is, a preparation method of the wear-resistant polymer material comprises the following steps:
[0061] S1. Weigh polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, lubricant, mineralizer, and mineral powder in proportion, stir at 400 r / min for 15 min to obtain a mixture;
[0062] S2. The mixed material is added into a twin-screw extruder, melted at 175° C., and extruded through a die of the extruder and cut into granules of 3 mm in size to obtain a wear-resistant polymer material.
[0063] Performance Testing
[0064] The wear-resistant polymer materials prepared in Examples 1-5 and Comparative Examples 1-5 were tested for friction and mechanical properties, wherein the friction performance test was performed by determining the friction coefficient and mass wear amount with reference to "GB / T 3960-2016 Test Method for Sliding Friction and Wear of Plastics", the test was repeated 3 times, and the average values were recorded in Table 1. The mechanical property test was performed by determining the tensile strength and elongation at break with reference to "GB / T 1040.1-2018 Determination of Tensile Properties of Plastics Part 1: General Principles", the test was repeated 3 times, and the average values were recorded in Table 1.
[0065] Table 1
[0066]
[0067] It can be seen from Table 1 that Examples 1-5 of the present invention have better friction performance and mechanical properties, especially Example 3 has better performance.
[0068] Compared with Comparative Example 1, the bone morphogenetic protein in the mineralizer of Example 3 is combined with the mineral components in the mineral powder, so that the mineral components can form an orderly arrangement inside the polymer material, thereby promoting the mineralization of the polymer material. The formation of this ordered structure not only significantly improves the interfacial bonding force between the mineral components and the polymer matrix, but also further promotes the mineralization degree of the polymer material, so that the overall strength and wear resistance of the material are also effectively improved. The mineralization inducing polypeptide in the mineralizer has the characteristic of high affinity with the mineral components. When the mineralization inducing polypeptide is mixed with the mineral powder, it can be selectively adsorbed on the surface of the mineral particles to form an orderly "guide layer". This guide layer not only stabilizes the mineral particles, but also provides guidance for their orderly arrangement in the polymer material matrix, and induces the polymer material to begin mineralization. With the guidance of the mineralization inducing polypeptide, the mineral particles begin to be deposited in an orderly manner in the polymer material matrix. The interaction between the mineralization inducing polypeptide and the polymer chain promotes the close combination between the mineral particles and the polymer material, and at the same time induces the polymer material to further mineralize. This orderly deposition and mineralization process forms a strong interface bond, which not only enhances the adhesion between mineral particles and polymer materials, but also makes the entire structure more compact, stable and wear-resistant due to the mineralization of polymer materials. Under the combined effect of the orderly arrangement and deposition of mineral particles and the mineralization of polymer materials, the performance of the polymer material matrix has been significantly improved, especially the strength and wear resistance have been significantly enhanced. The EDTA can form a stable complex with the metal ions in the mineral powder, effectively controlling the release rate of metal ions, thereby regulating the dynamics of the entire mineralization process. In the early stage of mineralization, EDTA can slowly release metal ions, providing a stable ion source for the nucleation and growth of the mineral phase. As the mineralization process proceeds, the chelation effect of EDTA gradually weakens, so that the release rate of metal ions matches the growth rate of the mineral phase, thereby ensuring the smooth progress of the mineralization process. In addition to controlling the release rate of metal ions, EDTA can also induce polymer materials to form mineral phases with specific structures and morphologies through complexation with metal ions. During the mineralization process, the complexes formed by EDTA and metal ions can serve as templates or guides for the growth of mineral phases. These complexes can guide the polymer chain segments to arrange and orient in a specific direction, thereby forming an ordered mineral phase structure. This ordered mineral phase structure significantly enhances the mechanical properties and friction properties of polymer materials.
[0069] Compared with Comparative Example 2, Example 3 shows that the mineralization-inducing polypeptide is a key component in the mineralizer. If it is missing, the function of the mineralizer will be significantly weakened, resulting in a significant decrease in the mineralization ability of the polymer material, thereby significantly reducing the mechanical properties and friction properties of the material. Therefore, only under the synergistic effect of bone morphogenetic protein, mineralization-inducing polypeptide, and EDTA, can the mineralizer exert its best performance and better induce the mineralization of the polymer material.
[0070] Compared with Comparative Example 3, the nanocellulose in Example 3 can provide a large number of reaction sites, creating favorable conditions for the nucleation and growth of mineral components. In the mineralization process, nanocellulose acts as a carrier to guide the mineral components to deposit in an orderly manner on its surface, thereby forming a highly ordered mineral structure. At the same time, when nanocellulose is composited with a polymer material, its nanoscale size enables it to fill in the gaps between polymer chains, enhancing the interaction between polymer chains, thereby improving the overall mechanical properties of the material.
[0071] Compared with Example 4, Example 3 shows that the plant fiber in Example 3 can effectively adsorb and enrich mineral components, and the complex porous structure of the plant fiber provides an ideal place for the nucleation and growth of minerals. These pores and fiber surfaces can serve as carriers for mineral deposition, guiding the orderly growth of minerals in specific positions and directions. In addition, the plant fiber also has good mechanical properties and flexibility, and can effectively enhance the strength and toughness of polymer materials. During the mineralization process, the plant fiber and the polymer material are intertwined to form a stable network structure, thereby improving the overall performance of the material.
[0072] Compared with Example 5, mineralization is not just a simple physical mixing process, but a complex chemical reaction and structural adjustment process, which plays a vital role in improving the mechanical properties and friction properties of polymer materials. First, the mineralization process can promote the chemical reaction between mineral powder and polymer materials to form a strong chemical bond. This bonding action significantly enhances the binding force between polymer chains and mineral particles, thereby improving the mechanical properties of the material. Secondly, the temperature and pressure conditions in the mineralization process help the rearrangement and orientation of polymer chains to form a more ordered and compact structure. This ordered structure can reduce defects and voids inside the material, improve the density and uniformity of the material, and then improve the strength and wear resistance of the material. Therefore, if there is no mineralization process, the mineralizer, mineral powder and other raw materials are simply mixed and melt granulated, then these excellent properties will not be formed. More importantly, the mineralization process can also change the surface properties of polymer materials. Through mineralization, a mineral layer can be formed on the surface of the polymer material, which not only improves the hardness of the polymer material, but also reduces the wear amount of the polymer material during the friction process, thereby significantly improving the wear resistance of the polymer material.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant polymer material, characterized in that: The wear-resistant polymer material comprises the following raw materials in parts by weight: 30-50 parts of polyurethane resin, 5-15 parts of nanocellulose, 10-20 parts of plant fiber, 20-40 parts of mineral powder, 5-10 parts of plasticizer, 5-10 parts of filler, 3-5 parts of lubricant, and 3-5 parts of mineralizer, wherein the mineralizer comprises bone morphogenetic protein, mineralization inducing polypeptide, and ethylenediaminetetraacetic acid; the mineralization inducing polypeptide is obtained by the following method: cleaning, sterilizing, and grinding shells into powder to obtain shell powder, and soaking the shell powder in a sodium hydroxide solution for 15-20 hours, wherein the mass volume ratio of the shell powder to the sodium hydroxide solution is (g / mL) (1.0-1.5): (3 .0-5.0), using ultrasonic equipment to treat the soaked shell powder, ultrasonically treating for 60-90 min under the conditions of ultrasonic power of 200-400W and ultrasonic frequency of 20-40kHz, using a 100-200 mesh sieve to filter the above solid-liquid mixture, taking the filtrate, extracting the filtrate with ethanol, the volume ratio of filtrate to ethanol is (1.0-1.2):(1.5-2.5), extracting 2-3 times to obtain a polypeptide solution, concentrating the polypeptide solution at 0.05-0.10MPa for 40-60min, and freeze-drying at -40 to -60°C for 100-120min to obtain a mineralization-inducing polypeptide; The method for preparing the wear-resistant polymer material comprises the following steps: S1. Weigh the polyurethane resin, nanocellulose, plant fiber, plasticizer, filler, and lubricant in proportion, and stir at 300-500 r / min for 10-20 min to obtain a mixture Ⅰ; S2. The mixture Ⅰ is added to a twin-screw extruder for a first melting to obtain a molten material Ⅰ; S3. Cool the molten material Ⅰ to 40-50 ℃, add mineralizer and mineral powder, stir at 100-200r / min for 20-30min to obtain a mixture Ⅱ, and put the mixture Ⅱ into a reactor for mineralization reaction; S4. Add the mineralized mixture II to the melt granulator for a second melting, and extrude the molten material through the die of the extruder and cut it into granules with a size of 2-4 mm to obtain a wear-resistant polymer material.
2. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The first melting in S2 is carried out at 150-200°C, and the second melting in S4 is carried out at 180-220°C.
3. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The mineralization temperature in S3 is 60-80°C, the mineralization pressure is 10-20MPa, and the mineralization time is 4-6h.
4. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The mineral powder is one or a combination of barite powder, corundum powder, feldspar powder, wollastonite powder, mica powder, talc powder and quartz powder.
5. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The plasticizer is one of dibutyl phthalate, epoxy soybean oil, dioctyl sebacate, trioctyl trimellitate, triethyl citrate and chlorinated paraffin.
6. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The filler is one or a combination of nano silicon dioxide, carbon fiber, glass fiber, and aluminum borate whisker.
7. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The lubricant is one or a combination of silicone oil, glycerol, fatty acid amide, oleic acid, and silicone powder.
8. The method for preparing a wear-resistant polymer material according to claim 1, characterized in that: The mineralizer is composed of bone morphogenetic protein, mineralization inducing polypeptide and ethylenediaminetetraacetic acid in a mass-to-volume ratio of g / mL (1-3):(4-8):(1-3).
9. A wear-resistant polymer material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
